The Application of STEM Education Approach in Inquiry-Based Physics Learning with Contextualization of Local Wisdom to Improve Science Process Skills - Prasetyo, Erwin; Rusdin, Muhamad Epi; Sina, Tuti Asmiranti; Sulisworo, Dwi; Al Farizi, Zakaria; Iftitah, Nur (Indonesian Review of Physics, 2024)
Education in Indonesia, particularly in eastern regions, faces significant challenges in preparing students to meet the demands of the 21st century. Conventional teaching methods often fail to effectively enhance science process skills, which are critical in the era of Industrial Revolution 4.0 and Society 5.0. This study aims to examine the effectiveness of a STEM Education approach combined with inquiry-based learning and the contextualization of local wisdom in improving students' science process skills. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects were students from four schools in Lembata Regency, namely SMA N Lebatukan, SMA N 1 Nubatukan, SMA N 2 Nubatukan, and MAN Lembata, East Nusa Tenggara, selected using purposive sampling. Data were analyzed using t-tests to evaluate significant differences between the two groups and effect size analysis to measure the impact of the treatment. The results showed a significant improvement in science process skills in the experimental group compared to the control group (p < 0.0001). The highest average score was achieved by SMA N Lebatukan (59.46), while MAN Lembata recorded the lowest average score (50.9). These findings confirm that integrating STEM, inquiry, and local wisdom effectively enhances scientific skills and the relevance of learning for students.